Korenine slovenskega samospeva - Barbo, Matjaž (Muzikološki zbornik, 2006)
The article concentrates on two Linhart''s settings of poems from his Almanac (1781). Although these two pieces for more than 60 years precede the traditionally dated beginning of the Slovene solo song, their modest musical texture as well as their intimate character draw attention to the same aesthetic principles typical of mode examples of the genre they seem to be linked with through the performing-possibilities within the bourgeois salon circle as well.
Keywords: Linhart, Anton Tomaž, 1756-1795; meščanski saloni; samospev; slovenska glasba